THE NEED FOR CAPACITY BUILDING IN HUMAN RESOURCE MANAGEMENT RELATED ISSUES: A CASE STUDY FROM THE MIDDLE EAST (LEBANON) - El Mouallem, Lara; Analoui, Farhad (European Scientific Journal, ESJ, 2014)
The remarkable evolution in the twentieth century has been a result of a new perspective in understanding the importance of investing in individuals and organizational human resources, and the implementation of capacity building strategies in various organizations and in societies. This paper explores the case of ICO, an international consultancy organization, based in the Middle East, specialized in architecture, engineering, planning, environment and economics. This qualitative study, using thirteen selected semistructured interviews, observations, and secondary data, has been conducted in the Beirut design office of the organization. The paper aims to examine major human resource related capacity building themes in ICO which include employee involvement and motivation, recruitment and selection, in addition to performance appraisal and reward management.